Algorithm for sizing parabolic-trough solar collectors - Nascimento, Fernanda I. [UNESP]; Zavaleta-Aguilar, Elí W. [UNESP]; Simões-Moreira, José R. (Elsevier, 2021)
This work aims at developing a working algorithm to evaluate the necessary parabolic-trough solar collectors (PTCs) sizing for any application, basically, as a function of the thermal load and the demanded operating temperature. Energy balance and heat transfer accurate estimations were applied to the PTC parts resulting in a set of non-linear equations, which were solved by a commercial software. Result analyses showed that a maximum relative error of 5.9% in PTCs lengthwise sizing and 6.1% in the thermal efficiency were achieved when compared to available data in the literature (experimental and theoretical ones), demonstrating that the algorithm is suitable for dimensioning both evacuated and not evacuated PTCs. Also, the PTC geometry and thermal efficiency sensitivity were analyzed as a function of relevant parameters, showing the required PTC length increased and the thermal efficiency decreased as either the following parameters were reduced: the direct solar irradiation, the PTC width, the receiver absorptivity and the heat transfer fluid (HTF) mass flow rate (in laminar and transitional flow regime) or the following parameters were increased: the receiver emissivity, the useful heat and the HTF outlet temperature. Also, three commercial thermal fluids were analyzed along with pressurized water. It was shown that water had a superior performance up to an outlet temperature of 300 °C. For temperatures above 400 °C, the required PTC length increased rapidly. The use of an evacuated receiver can reduce the PTC length between 9% up to 160% depending on the analyzed variable.
Keywords: Algorithm; Parabolic trough collector; Sizing; Solar energy